Structural Basis for Sirtuin Function: What We Know and What We Don’t - Sanders, Brandi D. (2009)
The sirtuin (silent information regulator 2) proteins are NAD(+)-dependent deacetylases that are implicated in diverse biological processes including DNA regulation, metabolism and longevity. Homologues of the prototypic yeast Sir2p have been identified in all three kingdoms of life, and while bacteria and archaea typically contain one to two sirtuins, eukaryotic organisms contain multiple members. Sirtuins are regulated in part by the cellular concentrations of the noncompetitive inhibitor, nicotinamide, and several synthetic modulators of these enzymes have been identified. The x-ray crystal structures of several sirtuin proteins in various liganded forms have been determined. This wealth of structural information, together with related biochemical studies, have provided important insights into the catalytic mechanism, substrate specificity, and inhibitory mechanism of sirtuin proteins. Implications for future structural studies to address outstanding questions in the field are also discussed.